Flexible Work Arrangements (FWA) dan Era Pasca-Pandemi: Tinjauan Bibliometrik terhadap Tren Penelitian Global - Madurani, Dina Noval; Rahmamita, Deane; Kariza, Nadya; Yolanda, Ledy; Fatikhah, Sabna Ainazah (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The rapid transformation of work patterns due to the COVID-19 pandemic has intensified scholarly interest in Flexible Work Arrangements (FWA), making it a critical topic in recent academic discourse. This study aims to explore trends and developments in FWA research over the past five years (2020–2025) through a bibliometric analysis using R Studio. A total of 135 selected articles from the Scopus database were analyzed using citation analysis, bibliographic coupling, and co-authorship mapping to examine topical evolution, identify influential research and authors, and understand patterns of academic collaboration in FWA studies. The findings reveal a significant rise in FWA-related publications, reflecting the global shift in work culture. The United Kingdom, Australia, and the United States lead in global publication output, with strong contributions from institutions such as Edith Cowan University and the University of Rome Tor Vergata. Prominent scholars, including Kelliher C, and leading journals in management and human resources have shaped the core discourse on FWA. However, the study also highlights a notable research gap in contributions from developing countries, including Indonesia. These findings underscore the need for further contextual and evidence-based research to inform adaptive and inclusive FWA policies amid a continuously evolving global work landscape.